Selective inhibition of interleukin 2 gene function following thymocyte antigen/major histocompatibility complex receptor crosslinking: possible thymic selection mechanism. - Ramarli, D (1986)
Considerable evidence now exists to support the notion that the 50-kDa sheep erythrocyte-binding protein, T11, represents an essential cell surface component of a human T-cell lineage activation pathway. Furthermore, it is known that the human T3-Ti T-cell antigen/major histocompatibility complex receptor complex is capable of regulating cell growth mediated by the T11 structure. Here we show that, within the T3+ thymocyte compartment, T3-Ti crosslinking rapidly inhibits T11-initiated interleukin 2 (IL-2) gene transcription and translation. This inhibition is restricted to the IL-2 gene (IL2) as transcription of both the IL-2-receptor gene (IL2R) and the Ti beta-chain gene (TCRB) are not affected (human gene designations are in parentheses). Perhaps more importantly, T3-Ti-mediated IL-2 inhibition of this type is not operational in peripheral T lymphocytes. The results imply that the majority of T3+ thymocytes are functionally distinct from peripheral T lymphocytes despite their T3+ phenotype and must possess a unique endogenous regulatory component for suppressing IL-2 gene activity. Moreover, since IL-2 is likely rate-limiting for growth within the thymus, the findings provide one plausible mechanism for thymic selection--namely, T3-Ti crosslinking of thymocytes upon interaction with self-major histocompatibility complex inhibits clonal expansion of high-affinity autoreactive cells.